Analisis Perbandingan Sistem Pendukung Keputusan Metode SMART Dengan SAW Dalam Menentukan Penerima Beasiswa Yayasan - Andani, Sundari Retno; Sumarlin, S; Aritonang, Romulo P. (LPPM STIKOM Tunas Bangsa, 2024)
Foundation scholarships are an effective way to reduce the number of students dropping out of college. Foundation scholarships are funding for tuition fees by foundations for underprivileged but outstanding students. In determining objective scholarship recipients, a decision support system is needed. In this case, the author applies the SMART (Simple Multi Attribute rating Technique) and SAW (Simple Additive Weighting) methods. The criteria used in determining scholarship recipients are the Grade Point Average (GPA), parental income and number of dependents. To obtain the final result in the form of a ranking of scholarship recipients, a calculation is carried out using the SMART and SAW methods, then the results will be carried out a comparative analysis of the two methods.